Does fintech threaten Islamic banking performance in Indonesia? - Fatimah Ath Thahirah; Rahmatina Awaliah Kasri (Journal of Islamic Accounting and Finance Research, 2023)
Purpose - This study aims to examine the impact of P2P Lending on both conventional and Islamic banking performance in Indonesia.Method - It uses a panel data regression method with a random effect model, with a sample of 63 conventional banks and 12 Islamic banks in Indonesia during the 2016-2020 period. The dependent variable is ROA, while the independent variable is the number of P2P Lending companies.Result - The study found that Fintech P2P Lending does not affect the conventional banks’ performance and has a minimal effect on the aggregate banks' performance in Indonesia. However, interestingly, Fintech has a significant positive impact on the Indonesian Islamic banks’ performance. The result is consistent when GMM is used in the robustness model.Implication - The findings indicate the importance of supporting the development of Fintech, especially Sharia P2P Lending, and collaboration between Fintech and banks to optimize the performance of Indonesia’s financial sector.Originality - This research is amongst a few studies that examine the relationship between Fintech and banking performance, particularly Islamic banking performance in Indonesia.